1997
DOI: 10.1002/elps.1150181538
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plasma proteins facilitated by enrichment on particulate surfaces: Analysis by two‐dimensional electrophoresis and N‐terminal microsequencing

Abstract: Plasma protein adsorption on intravenously injectable drug carriers is regarded as an important factor for the fate of the particles in the body after their administration. Therefore, the plasma protein adsorption patterns on a number of different carrier systems were analyzed in vitro employing two-dimensional electrophoresis (2-DE). The particulate systems presented in this study were polystyrene (PS) model particles, PS nanoparticles surface-modified by adsorption of a surfactant, a commercial fat emulsion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…PEG-and poloxamine-coated nanocarriers have been demonstrated to undergo immunoglobulin, fibronectin, and apolipoprotein association [14, 29, 33, 118, 122124, 147] as well as C3 opsonisation that mediates the biorecognition by macrophages through specific complement receptors (CR1 and CR3, CD11b/CD18) [18]. However, these systems possess long-lasting profiles in blood [148].…”
Section: The Opsonisation Processmentioning
confidence: 99%
“…PEG-and poloxamine-coated nanocarriers have been demonstrated to undergo immunoglobulin, fibronectin, and apolipoprotein association [14, 29, 33, 118, 122124, 147] as well as C3 opsonisation that mediates the biorecognition by macrophages through specific complement receptors (CR1 and CR3, CD11b/CD18) [18]. However, these systems possess long-lasting profiles in blood [148].…”
Section: The Opsonisation Processmentioning
confidence: 99%
“…Spots on 2-DE can be used for protein sequencing using an automatic gas phase sequencer 7479 . A successful sequence of a peptide of 10–30 N-terminal amino acids residues can determine the identity of the protein through database search 79 .…”
Section: Np-proteome Interactionsmentioning
confidence: 99%
“…In previous studies a preferential adsorption of proteins from human plasma could be shown, i.e., enrichment of certain proteins on particulate surfaces while others are diminished compared with their concentration in the bulk medium. [7][8][9][10][11][12] Because the in vivo fate of intravenously administered nanoparticles is strongly influenced by interactions with blood components, enrichment of certain proteins might be able to direct the particles to specific target cells or tissues. Exemplarily, this could be shown for particles with ApoE enrichment on the surface to target drugs to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…and the significance of protein adsorption for the behavior of, e.g., intravenously administered particulate drug carriers. [1][2][3][4][5][6][7][8][9] These carriers are one approach to the sitespecific delivery of drugs, and the immunological recognition by cells of the mononuclear phagocyte system (MPS) is a major obstacle for their application. In previous studies a preferential adsorption of proteins from human plasma could be shown, i.e., enrichment of certain proteins on particulate surfaces while others are diminished compared with their concentration in the bulk medium.…”
Section: Introductionmentioning
confidence: 99%